08bAss4sol - AS3sol/MATH1111/YKL/08-09 THE UNIVERSITY OF...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: AS3sol/MATH1111/YKL/08-09 THE UNIVERSITY OF HONG KONG DEPARTMENT OF MATHEMATICS MATH1111: Linear Algebra Assignment 4 Suggested Solution 1. (a) It is because N ( B ) ⊂ N ( AB ). (See Tutorial 7 Ans for Qn 1 (a) i). (b) When rank( A ) = n , dim N ( A ) = n- rank( A ) = 0. i.e. N ( A ) = { } . This implies ( * ): A x = has trivial solution only. (i.e. If A x = , then x = .) Let u ∈ N ( AB ). Then A ( B u ) = AB u = . By ( * ), B u = . i.e. u ∈ N ( B ), or in other words, N ( AB ) ⊂ N ( B ). Hence we conclude N ( B ) = N ( AB ), thus rank( AB ) = r- dim N ( AB ) = r- dim N ( B ) = rank( B ) . 2. (a) As A is row equivalent to 1 1 2 0 1 1 0 0 0 , the two columns (1 0 1) T , (1 1 3) T form a basis for c ( A ). Also, N ( A ) = Span((- 1- 1 1) T . Direct checking shows that 1 1 , 1 1 3 , - 1- 1 1 are linearly independent. So c ( A ) + N ( A ) = R 3 . It is also easy to see that c ( A ) ∩ N ( A ) = { } . (You may check it directly or use the formula in Assignment 3 Qn. 4, dim c ( A ) = 2, dim N ( A ) = 1 so dim( c ( A ) ∩ N ( A )) = 0.) Hence c...
View Full Document

Page1 / 3

08bAss4sol - AS3sol/MATH1111/YKL/08-09 THE UNIVERSITY OF...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online